Anti-Poly(glycerolphosphate) in Human Sera - Doyle, Ronald J. (1982)
Ultrasonic extracts from staphylococci contained red cell-sensitizing poly(glycerolphosphate)teichoic acid antigen. The antigen may contribute to the variability of precipitin reactions used in the diagnosis of Staphylococcus aureus infection.